RFID Security Protocol Based On Cryptographic Hash Function (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Radio Frequency Identification (RFID) is a technology for  automated identification of objects and people. RFID consists of  the tags, one or more readers, and a backend database. RFID  Tags are tuned to a particular frequency, and each tag has a  unique ID. The communication between RFID tag and Reader  implements wireless communication, which is considered risky  and easily attacked. RFID protocol conquers a forward privacy problem but presumed  that communication channel between reader and database is  secure, which doesn't agree with the real development of IOT. To  conquer the privacy drawbacks of RFID protocol in mobile  environment, an RFID security protocol based on the  cryptographic hash function is design. This paper summarizes the problem about RFID security in the  environment of IOT and suggests effective RFID security  protocol based on cryptographic hash function. The suggested  work will raise security to somewhat measure as well as denial of-service attack (DoS attack) and man-in-the-middle attack  (MITM attack), while hold on to a reasonable computation cost.
Keywords: RFID protocol; RFID tag; forward privacy; cryptographic hash function; DoS attack; MITM; attack; IOT